Improving the Ability Read the Qur'an Through the Tahsin Method Based on the Learn Quran Tajwid Application for Students at MTs Putra DDI Mangkoso - Arini Fitri; Muh. Dahlan; Muzdalifah Muhammadun; Usman; Muh. Akib D (Universitas Muhammadiyah Palu, 2024)
Preliminary studies revealed that the Qur'an learning (Tajwid) conducted at MTs Putra DDI Mangkoso still used less varied teaching methods such as lecture methods, causing students to lack enthusiasm and feel bored during lessons. The lack of students' attention to learning will impact their unsatisfactory ability to read the Qur'an. The aim of this research is to determine: 1) Differences in the ability to read the Qur'an among students before and after using the Tahsin method based on the Learn Quran Tajwid application, 2) The improvement of the ability to read the Qur'an through the Tahsin method based on the Learn Quran Tajwid application for students at MTs Putra DDI Mangkoso. This study is a quantitative research using a Quasi-Experimental Design with a Pretest-Posttest Control Group Design. The study consists of an experimental group and a control group randomly selected from two classes, VIIIb and VIIIc, chosen purposively and processed using the Random Sampling method. The research sample consisted of 30 students, 15 in the experimental class and 15 in the control class. Results of the study: 1) The initial ability of students to read the Qur'an, especially in Tajwid, is still lacking. Most students face challenges in understanding Tajwid material, such as tasydid, mad, waqaf, and gunnah. After using the Tahsin method through the Learn Quran Tajwid application, focusing on material features such as harokat letters, basic Tajwid, and advanced Tajwid, there was an improvement in test results. In the experimental class, the pretest average score increased from 64.33 (less good category) to 86.67 (very good category) after the posttest. Meanwhile, in the control class, the pretest score increased from 62.00 (less good category) to an average of 68.67 (sufficient category) after the posttest. 2) The use of the Tahsin method based on the Learn Quran Tajwid application effectively improved the ability to read the Qur'an for students. The N-Gain Score calculation aims to determine the effectiveness of the improvement in using a method or treatment. In the experimental class, the N-Gain Score was 65.27, categorized as quite effective in improving the ability to read the Qur'an, while in the control class, the N-Gain Score obtained was 16.95, categorized as not effective in improving the ability to read the Qur'an. Thus, the use of the Tahsin method based on the Learn Quran Tajwid application, focusing on harokat letters, basic Tajwid, and advanced Tajwid materials, for students at MTs Putra DDI Mangkoso, can enhance the ability to read the Qur'an and is effectively used.